Leadership 4.0: Harnessing Technology and Humanity for Effective Management - Abhinav, Sharadha. S (Journal of Informatics Education and Research, 2024)
The Fourth Industrial Revolution, characterized by the convergence of digital technologies, has initiated a profound transformation in the landscape of leadership, giving rise to the concept of Leadership 4.0. This new paradigm emphasizes the integration of technology and humanity for effective management in the digital age. While emerging technologies like artificial intelligence, data analytics, and automation offer immense potential for driving efficiency and growth, they also present profound ethical challenges related to privacy, bias, and social impact. As organizations navigate this digital disruption, ethical leadership emerges as a critical guiding principle, necessitating the establishment of clear ethical frameworks and the prioritization of human well-being. However, there exists a research gap in understanding how leaders can effectively navigate the ethical complexities of emerging technologies within the framework of Leadership 4.0. While there is growing recognition of the importance of ethical leadership in the digital age, there remains a lack of comprehensive studies that specifically address the intersection of ethical leadership and emerging technologies. This research highlights the need for future research to bridge this gap and provide insights into how leaders can navigate the challenges and opportunities presented by the Fourth Industrial Revolution while prioritizing human well-being.